THE VIOLATION OF GRICE'S MAXIMS OF COOPERATIVE PRINCIPLE IN A TELEVISION COMEDY OPERA VAN JAVA (OVJ) - Ai Dini Mulyani, - (2011)
This research is entitled "The Violation of Grice's Maxims of Cooperative Principle in a Television Comedy Opera Van Java (OVJ)". The study was aimed to investigate the maxim of CP that was mostly violated in the comedians' dialogues and to analyze how the violations were made in the dialogues. This study employed descriptive qualitative method to analyze the collected data. The data were analyzed based on the theory of cooperative principle proposed by Grice (1975). In analyzing the data, the researcher conducted several steps: recording the program on the TV, transcribing the script of the dialogues, analyzing the occurrence of the violations in each maxim, and observing the ways the comedians violated the maxims. The findings of the research show that the type of maxims that was dominantly violated was the maxim of quality. It was followed by the violation of maxim of manner, maxim of relation, and maxim of quantity. In addition, the findings also reveal that the violations of the maxims were made through several ways: giving false information, giving obscure expression, giving irrelevant response, giving more information, giving less information, giving unnecessary verbosity, and asking irrelevant question. These findings show that in the show, the comedians tended to use 'deceit' (untrue utterances and actions) in creating their jokes.